Chronology and the new National Curriculum for history: is it time to refocus the debate?. Issue 6 (19th September 2018) - Hodkinson, Alan; Smith, Christine
ABSTRACT: Coming some four years after the introduction of the new National Curriculum, this article considers the media storm and debate around the concept of chronology and how it should be taught in schools. Drawing on empirical evidence, the article strongly suggests that young children are capable of grasping complex temporal concepts, specifically chronology, if teachers carefully plan for their development through targeted activities. Within the article suggestions for such activities, including whole-school approaches, are outlined. In conclusion, the article calls for further research into how history can be taught in a way that develops chronology and engenders a love for and enjoyment of the subject by all pupils in our primary schools.